Parechovirus neonatal sepsis and meningitis - a (still) poorly recognised agent - Raquel Garrido; Joana Antunes; Helena Pedroso; Madalena Fialho; Manuel Cunha (Hygeia Press di Corridori Marinella, 2021)
Human parechovirus (HPeV), a Picornaviridae virus, is a microorganism associated with respiratory and gastrointestinal infections, in most cases with a benign clinical course. However, some serotypes have been recently associated with a more serious clinical outcome in young children, namely sepsis-like disease and meningitis. In this report, we describe the case of a previously healthy, 11-day-old infant in our Paediatric Emergency Department who presented with high fever, irritability and poor feeding. No other accompanying symptoms, such as respiratory, gastrointestinal or urinary, were shown by the patient. Family history unveiled an 18-month-old sibling with an upper respiratory tract infection. Physical examination was unremarkable. Laboratory testing revealed a normal total white cell count with lymphopenia and a maximum C-reactive protein value of 21.4 mg/L. Cerebrospinal fluid (CSF) analysis showed pleocytosis with high proteinorrachia and normal glycorrhachia. With the clinical suspicion of sepsis, she was hospitalized for clinical surveillance, and empirical antibiotics were administered. Although the bacteriological exams of blood and CSF were negative, RNA of an HPeV was detected in the CSF. She had a favourable clinical course, the cerebral ultrasound was normal, and the clinical follow-up showed adequate psychomotor development until today (18 months old). Recent publications suggested HPeV as one of the major agents of neonatal sepsis and meningitis. Similarly, several other studies reported significant neurological impairments in infants with HPeV infection. In line with these recent findings, we believe this clinical case further supports the need for more extensive research in viral aetiology and in particular of this, not so uncommon, agent in order to avoid unnecessary and potentially harmful interventions in newborns presenting with a sepsis-like clinical picture.